The 80th Anniversary of Cortical Spreading Depression of Leao: A Major Component in Experimental and Clinical Neuropathology - Avraham Mayevsky (British Journal of Healthcare and Medical Research, 2023)
Understanding of the mechanisms behind brain neuropathology is a major factor in diagnosis as well as treatment of patients. The discovery of the reversible event of cortical spreading depression (CSD) in conjunction with epileptic activity led a new era in better understanding of brain pathology. Eighty years ago, A.A.P. Leao discovered this unique response, of the cerebral cortex of animals, to mechanical, chemical or electrical stimulation. A single CSD wave that propagate in the rate of 3-6 mm/minute includes electrical, ionic, circulatory and metabolic responses. The metabolic changes include activation of oxygen consumption as evaluated by monitoring of mitochondrial NADH redox state. It was found that CSD could be developed spontaneously after various perturbations such as moderate hypoxia or ischemia, epileptic activity, hyperbaric oxygenation, head injury and brain retraction. Our conclusion is that better clinical monitoring of the brain that will detect the appearance of CSD will improve patient’s care in critical situations.